Sitagliptin attenuates cardiomyopathy by modulating the JAK/STAT signaling pathway in experimental diabetic rats - Al-Rasheed NM; Al-Rasheed NM; Hasan IH; Al-Amin MA; Al-Ajmi HN; Mahmoud AM (Dove Medical Press, 2016)
Nouf M Al-Rasheed,1 Nawal M Al-Rasheed,1,2 Iman H Hasan,1 Maha A Al-Amin,1 Hanaa N Al-Ajmi,1 Ayman M Mahmoud3 1Department of Pharmacology and Toxicology, College of Pharmacy, King Saud University, 2Department of Pharmaceutical Sciences, College of Pharmacy, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 3Physiology Division, Department of Zoology, Faculty of Science, Beni-Suef University, Beni-Suef, Egypt Abstract: Sitagliptin, a dipeptidyl peptidase-4 inhibitor, has been reported to promote cardioprotection in diabetic hearts by limiting hyperglycemia and hyperlipidemia. However, little is known about the involvement of the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway modulation in the cardioprotective effects of sitagliptin. The current study aimed to investigate the protective effects of sitagliptin against diabetic cardiomyopathy (DCM), focusing on the modulation of the JAK/STAT pathway. Diabetes was induced by streptozotocin injection, and rats received sitagliptin orally and daily for 90 days. Diabetic rats exhibited hyperglycemia, hyperlipidemia, and a significant increase in heart-to-body weight (HW/BW) ratio. Serum troponin I and creatine kinase MB, cardiac interleukin-6 (IL-6), lipid peroxidation, and nitric oxide levels showed significant increase in diabetic rats. In contrast, both enzymatic and nonenzymatic antioxidant defenses were significantly declined in the heart of diabetic rats. Histopathological study revealed degenerations, increased collagen deposition in the heart of diabetic rats. Sitagliptin alleviated hyperglycemia, hyperlipidemia, HW/BW ratio, histological architecture, oxidative stress, and inflammation, and rejuvenated the antioxidant defenses. In addition, cardiac levels of pJAK2 and pSTAT3 were increased in diabetic rats, an effect which was remarkably decreased after sitagliptin treatment. In conclusion, these results confer an evidence that sitagliptin has great therapeutic potential on DCM through down-regulation of the JAK/STAT signaling pathway. Keywords: diabetic cardiomyopathy, DPP-4 inhibitors, JAK/STAT, oxidative stress, inflammation